DOMESTIC TRENDS IN THE DEVELOPMENT OF PUBLIC-PRIVATEPARTNERSHIPS IN THE FIELD OF VOCATIONAL EDUCATION ANDTRAINING (Innovative professional education, 2024)
Based on the analysis of current legislative, regulatory and legal documents, scientific sources and practical experience, the main trends in the development of public-private partnership in the field of vocational education in Ukraine are identified, namely: the useof social partnership mechanisms based on agreements and cooperation of vocational education institutions with sectoral and regional councils; implementation of national and regional projects in accordance with market needs; increase in international projects of the European Union countries to expand investment in the development of vocational education and training; application of strategic management tools for the development of vocational education and training institutions, taking into account regional socio-economic strategies; increase in the competitiveness and attractiveness of vocational education and training institutions based on the development of their intellectual and resource innovation potential; decrease in the motivation of business representatives to develop public-private partnerships in the field of vocational education and training, due to the insufficient definition of the legal status of participants and the lack of clear mechanisms for regulating relations in force majeure at a certain stage of the implementation of a public-private partnership project.
Keywords: public-private partnership, vocational education, labor market, professional standards